Fabrikasi Elektroda Karbon Dengan Prinsip Kapasitif Untuk Menurunkan Kadar Garam Dalam Air Yang Ditandai Dengan Penurunan Nilai TDS (Total Dissolved Solid) - Putro, Triswantoro (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2017)
Desalination is a method for converting sea air into fresh air. One of the eco-friendly and energy saving method is to use carbon electrodes with capacitive principles. A fabricated carbon electrode using a mixture of activated carbon and PVA uses ratio composition 20:1. The mixture of the material is printed on a graphite sheet 80 x 60 x 0.5 mm3. The desalination process takes 2 cycles of adsorption and desorption. The adsorption cycle is a cycle when electrode is fed. The ions will be attracted to the electrode and the salt in the air will be reduced. While desorption cycle is the cycle when the electrode voltage is detached and the ions adhered on adsorption cycle will be detached. The result of TDS which is used as the sample water salt measurement shows that the reduction of TDS value is 32,5% from the formerly condition. The temperature measurement of water sample during desalination process shows that the temperature does not have any changing.